Faktor-Faktor Penentu yang Mempengaruhi Niat Penggunaan Mobile Payment - Limantoro, Eric Prasetya; Anandya, Dudi (Jurnal Bisnis dan Manajemen, 2022)
The purpose of this study is to examine the effect of Perceived Security, Perceived Compatibility, User Mobility, Personal Innovativeness, Social Norms, and Social Self Image on Intention To Use Mobile Payment on Gopay consumers in Surabaya. This study using a sample of 170 Gopay customers in Surabaya where at the time of sampling using a non probability sampling technique that is Sampling Purposive, then data was collected using an online questionnaire method and this research was conducted using the Structural Equation Model (SEM). The results showed that Perceived Security, Perceived Compatibility, User Mobility has a significant positive effect on Perceived Usefulness but for Personal Innovativeness it did not have a positive effect on Perceived Usefulness as a mediation, while for the mediating effect of Perceived Ease Of Use, the results showed that Perceived Security, Perceived Compatibility, User Mobility did not positive effect but Personal Innovativeness has a significant positive effect on Perceived Ease Of Use, for the results the mediation effect of Perceived Usefulness and Perceived Ease Of Use does not affect the relationship between Perceived Security, Perceived Compatibility, User Mobility, Personal Innovativeness on Intention To Use Mobile Payment, lastly for the influence of social norms and social self image has a significant positive effect on Intention To Use Mobile Payment.